Optimizing community-based aquaponics: Evaluating the impact of rotary drum filter implementation on water conservation and operational efficiency - Muhammad Fuad; Arief Budihardjo Mochamad; Shofwan Agus; Sumartono Agus; Setyawan Budi; Inandin Nabiha Puteri (E3S Web of Conferences)
This study investigates the application of a Rotary Drum Filter (RDF) in a community-based aquaponic system, focusing on its impact on water conservation, operational efficiency, and economic viability. The RDF, incorporating a 200 mesh screw made from stainless steel 316 (SS 316) and a casing of polypropylene (PP), is designed for enhanced durability and chemical resistance. Key parameters such as water inlet and outlet diameters, body dimensions, and flow rate were optimized to suit the specific needs of a small to medium-sized aquaponic system. The implementation of the RDF resulted in significant water savings, reducing the need for frequent water replacement while maintaining high water quality. The compact design of the RDF allowed for seamless integration into the existing system without requiring additional space. Moreover, the study highlights the RDF’s ability to minimize labor requirements, making it an ideal solution for community-driven projects with limited resources. The findings underscore the importance of advanced filtration technology in improving the sustainability and efficiency of community-based aquaponics, addressing the research gap in this underexplored area.